Enfermería: modos de cuidar del paciente con tratamiento de hemodiálisis - Díaz Castillo, Nancy Liliana (2019)
ABSTRACT Qualitative research whose objective was to describe and analyze the ways of care that the nurse performs for the patient with hemodialysis treatment. The theoretical bases that guided the study were: Human care by Boff, Nursing care by Waldow, Nursing comfort by Neves & Pereira; authors whose philosophical thinking allows to approach the study from the objective / subjective dimensions of nursing care. Seven nurses and seven patients with hemodialysis treatment participated. The data were obtained using the in-depth interview. Orlandi’s discourse analysis was used and was consided ethical criteria and scientific rigor. From the analysis of the speeches, two main categories emerged: I. Taking care from Uncomfort to the Comfort of the hemodialysis patient, with two sub categories: taking care of the patient-body-hemodialysis machine and educating for health. II. Caring with Love, Touch and Tenderness. Ways of caring that the nurse assists to contribute to the well-being and improve the quality of life of the patient with hemodialysis treatment, with technical, scientific, ethical and human competence.